MENGGAGAS INTERNASIONALISASI SMK : PELUANG DAN TANTANGAN MENUJU MASYARAKAT GLOBAL - Areli, Ahmad Jon; Agustina, Mediarita (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
The era of challenging globalization is a time of inevitability. For that educational institution, especially Vocational education must be able to answer the challenge by changing the direction and orientation of education. All stakeholders should be able to read opportunities and challenges. so that SMK graduates can be accepted as well as become the main supporting element in the world community, without losing the identity as a belief and cultured creature. SMK with global standardization, but not leaving local wisdom. That is the ideals conceived in this paper. The concrete form is the internationalization of SMK through the realization of a comprehensive, emancipative, competitive, inclusive, collaborative, and transformative education model.Keywords— internationalization, SMK, opportunities, challenges, global society